Microporous conjugated polymers via homopolymerization of 2, 5-diethynylthiophene. (July 2017) - Bondarev, Dmitrij; Sivkova, Radoslava; Šuly, Pavol; Polášková, Martina; Krejčí, Ondřej; Křikavová, Radka; Trávníček, Zdeněk; Zukal, Arnošt; Kubů, Martin; Sedláček, Jan
Graphical abstract: Highlights: Homopolymerization of 2, 5-diethynylthiophene into a microporous conjugated polymer. Microporous conjugated polymer by chain-growth homopolymerization. Microporous conjugated polymer by polycyclotrimerization reaction. Sulphur-rich microporous polymer. Abstract: Homopolymerizations of 2, 5-diethynylthiophene into conjugated microporous polymers by (i) chain-growth polymerization and (ii) polycyclotrimerization are described. Both methods provide nearly quantitative yields of thiophene-rich (7.6 mmol thiophene rings/g) networks with specific surface area up to 839 m 2 /g. The thiophene units enhance the affinity of the networks to CO2 and red-shift the UV/vis and fluorescence absorption and emission bands of the networks, respectively.